2020
DOI: 10.1007/s12178-020-09614-2
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic Product Treatments: Clinical and Basic Science Evidence

Abstract: Purpose of Review Orthobiologics, including amniotic products, have been gaining interest in the past decade for the treatment of various orthopedic conditions including osteoarthritis. However, the use of biologics is varied and is currently available with minimal oversight or regulation. This review will assess the current state of research that utilizes amniotic products both in vitro and in vivo. Recent Findings Amniotic tissue derivatives have been shown to have positive effects in animal models for a var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 34 publications
(33 reference statements)
0
19
0
Order By: Relevance
“…Placenta-derived products, including cryopreserved amniotic membrane (AM) and umbilical cord (UC), are currently being investigated given their commercial availability, long history of safe use, and their known antiinflammatory, anti-scarring, and pro-regenerative properties. [15][16][17][18] In a preclinical study, Raines et al 19 found that intra-articular injection of AM/UC particulate dose-dependently attenuates cartilage degeneration in a rat OA model. A recent prospective pilot study further demonstrated that one or two injections of 50 mg AM/ UC particulate significantly improved pain and physical function in mild knee OA for up to 6 months.…”
Section: Introductionmentioning
confidence: 99%
“…Placenta-derived products, including cryopreserved amniotic membrane (AM) and umbilical cord (UC), are currently being investigated given their commercial availability, long history of safe use, and their known antiinflammatory, anti-scarring, and pro-regenerative properties. [15][16][17][18] In a preclinical study, Raines et al 19 found that intra-articular injection of AM/UC particulate dose-dependently attenuates cartilage degeneration in a rat OA model. A recent prospective pilot study further demonstrated that one or two injections of 50 mg AM/ UC particulate significantly improved pain and physical function in mild knee OA for up to 6 months.…”
Section: Introductionmentioning
confidence: 99%
“…[ 140 ] Therefore, in recent years, extensive research has been performed to explore the application of decellularized human amniotic membrane and umbilical cord (AM/UC) for the treatment of chronic wounds. [ 141 ] These grafts are Epifix, originated from human amnion matrix, and Neox, originated from human AM/UC tissue. [ 142 ] Interestingly, amniotic membranes were not rejected by the immune system owing to human leukocyte antigen (HLA) expression.…”
Section: Immunomodulatory Hydrogels For Chronic Skin Woundsmentioning
confidence: 99%
“…Implanted acellular PM graft in a subcutaneous mouse model encouraged migration and infiltration of host cells during the healing process, specifically of fibroblast-like cells, macrophages, endothelial cells, and fewer T-cells than the control graft [ 77 ]. PM has been successfully used in ophthalmology for almost 30 years for the treatment of corneal lesions, retinal detachment, and limbal cell regeneration [ 78 , 79 ]. Both intact and denuded PM used in ocular reconstruction in a rabbit model achieved re-epithelialization and integration into the rabbit tissue by 3-weeks post-surgery, with lower inflammatory responses noted in denuded PM treated eyes [ 80 ].…”
Section: Placental Membranementioning
confidence: 99%